Kajian Penggunaan Serat Selulosa Alami Dari Daun Nanas (Serat Nanas) Sebagai Bahan Stabilizer Campuran Beraspal SMA - Putri, Yuliana; Santosa, Leo; Adiman, Edi Yusuf (Journal of Infrastructure and Construction Technology, 2023)
SMA asphalt mixture is an asphalt mixture with gap graded, so this type of pavement requires a high asphalt content. High asphalt content in the mixture has positive and negative impacts. The advantage is that it can make the mixture resistant easily oxidization and can make increase the durability of the road pavement layer. The disadvantage is prone to drain down (a condition where the binder (asphalt) will flow or separate from the mix) in the form of cellulose fibers or polymer fibers. This results in a mixture of SMA which is more resistant to deformation, deflection, and cracking and is stable to withstand the load of the vehicle's wheels. The additives commonly used are synthetic cellulose fibers, called Arbocell and Viatop66. This product is manufactured in Rosenberg-Germany. The use of this product causes problems, namely the high price and depends on the dollar price, and requires additional procurement costs in the form of import costs. Therefore, it is necessary to find an alternative to replace the cellulose fiber with natural fibers that have characteristics that are close to synthetic fibers. Based on the literature review, several natural cellulose fibers that have been successfully used as additives for SMA mixtures are rice bran fiber, palm fiber, coconut fiber, and pineapple leaf fiber, coconut fiber, kapok fiber, corn cobs. With cellulose content ranging from 14 – 64%, it shows good performance. Therefore, pineapple leaf fiber with a higher cellulose content of 69.5%-71.5% has the potential to be used as an additive because it has a cellulose content that is close to synthetic fiber.